BEST PRACTICE LITERASI DIGITAL NURUL IMAN “LIDI NURIM” - Rahayuningsih; Tauvan Nuswantari (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
This best practice was aimed to convey the author's experience in applying digital literacy to create a culture of literacy among students in grades 4, 5 and 6 at SD IT Nurul Iman. The strengthening of character education through a culture of digital literacy among students needed to be developed from an early age. The students who dominate elementary school now are Z generation and alpha generation, they are connected to the digital world in their daily lives. This motivated teachers to continue to transform and innovate so that the learning process is in line with the current generation's times. There are 2 instruments used in this best practice, namely observation sheets and questionnaires. There are two observation sheets, including: (1) Observation sheet to obtain data about the teacher's activities and role in implementing